The introduction of a midwife-led obstetric triage system into a regional referral hospital in Ghana. (June 2018) - Floyd, Liz; Bryce, Fiona; Ramaswamy, Rohit; Olufolabi, Adeyemi; Srofenyoh, Emmanuel; Goodman, David; Pearson, Nancy; Morgan, Kerry; Tetteh, Cecilia; Ahwireng, Victoria; Owen, Medge
Abstract: Objective: to introduce and embed a midwife-led obstetric triage system in a busy labour ward in Accra, Ghana to improve the quality of care and to reduce delay. Design: the study utilized a participatory action research design. Local staff participated in baseline data collection, the triage training course design and delivery, and post-training monitoring and evaluation. Setting: a regional referral hospital in Accra, Ghana undertaking 11, 032 deliveries in 2012. Participants: all midwives and medical staff. Measurements: measurements included maternal health outcomes, observations of labour ward activity, structured assessments of midwife actions during admission, waiting times, focus group discussions, and learning needs assessments which informed the course content. During training, two quality improvement tools were developed; coloured risk acuity wristbands and a one page triage assessment form. Participants measured compliance and accuracy in the use of these tools following course completion. Findings: initially, no formal triage system was in place. The environment was chaotic with poor compliance to existing protocols. Sixty-two midwives received triage training between 2013 and 2014. Two Triage Champions became responsible for triage implementation, monitoring and further training. Following training, the 'in-charge' midwives recorded a cumulative average of 83.4% of women wearing coloured wristbands. A separate audit by the Triage Champions found that 495/535 (93%) of the wristbands were correctly applied based on the diagnosis. Quarterly monitoring of the triage assessment forms by Kybele trainers, showed that 92% recorded the risk acuity colour, 85% a 'working diagnosis' and 82% a 'plan.' Median (interquartile range) waiting times were reduced from 40 (15–100) to 29 (11–60) minutes (p = 007). Twenty of 25 of the staff reported that the wristbands were helpful. Conclusions: an interactive triage training course led to the development of a triage assessment form and the use of coloured patient wristbands which resulted in delay reduction and improved quality of maternity care. Highlights: A tailored obstetric triage training programme reduced congestion and delay. Coloured wristbands proved an effective and sustainable triage prioritization tool. Local champions and collaborative QI projects were key to embedding best practice.